Cardiovascular disease in Down syndrome. Issue 5 (October 2018) - Versacci, Paolo; Di Carlo, Duccio; Digilio, Maria C.; Marino, Bruno
Abstract : Purpose of review: In the last 40 years, with a better understanding of cardiac defects, and with the improved results of cardiac surgery, the life expectancy of persons with Down syndrome has significantly increased. This review article reports on advances in knowledge of cardiac defects and cardiovascular system of persons with trisomy 21. Recent findings: New insights into the genetics of this syndrome have improved our understanding of the pathogenetic mechanisms of cardiac defects. Recent changes in neonatal prevalence of Down syndrome suggest a growing number of children with cardiac malformations, in particular with simple types of defects. Ethnic and sex differences of the prevalence of specific types of congenital heart disease (CHD) have also been underlined. A recent study confirmed that subclinical morphologic anomalies are present in children with trisomy 21, also in the absence of cardiac defects, representing an internal stigma of Down syndrome. The results of cardiac surgery are significantly improved in terms of immediate and long-term outcomes, but specific treatments are indicated in relation to pulmonary hypertension. Particular aspects of the cardiovascular system have been described, clarifying a reduced sympathetic response to stress but also a 'protection' from atherosclerosis and arterial hypertension in these patients. Summary: Continuing dedication to clinical and basic research studies is essential to further improve survival and the quality of life from childhood to adulthood of patients with trisomy 21.